2016
DOI: 10.1002/2016gl069922
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton blooms weakly influence the cloud forming ability of sea spray aerosol

Abstract: After many field studies, the establishment of connections between marine microbiological processes, sea spray aerosol (SSA) composition, and cloud condensation nuclei (CCN) has remained an elusive challenge. In this study, we induced algae blooms to probe how complex changes in seawater composition impact the ability of nascent SSA to act as CCN, quantified by using the apparent hygroscopicity parameter (κapp). Throughout all blooms, κapp ranged between 0.7 and 1.4 (average 0.95 ± 0.15), consistent with labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
79
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 78 publications
9
79
1
Order By: Relevance
“…At 50 nm the critical supersaturation of Sea Sweep samples (0.27–0.32%) was only slightly higher than pure NaCl particles (Figure ). This small depression in CCN activity was previously observed in mesocosm studies by Fuentes et al () (at OC concentrations <300 μM) and Collins et al (). Collins et al () concluded that these small changes in CCN activity would induce less than a 3% increase in expected CCN concentrations for typical marine cloud supersaturations.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…At 50 nm the critical supersaturation of Sea Sweep samples (0.27–0.32%) was only slightly higher than pure NaCl particles (Figure ). This small depression in CCN activity was previously observed in mesocosm studies by Fuentes et al () (at OC concentrations <300 μM) and Collins et al (). Collins et al () concluded that these small changes in CCN activity would induce less than a 3% increase in expected CCN concentrations for typical marine cloud supersaturations.…”
Section: Resultssupporting
confidence: 83%
“…This small depression in CCN activity was previously observed in mesocosm studies by Fuentes et al () (at OC concentrations <300 μM) and Collins et al (). Collins et al () concluded that these small changes in CCN activity would induce less than a 3% increase in expected CCN concentrations for typical marine cloud supersaturations. Note that the CCN/CN curves in Figure are much steeper than those reported by Quinn et al () for WACS‐1.…”
Section: Resultssupporting
confidence: 83%
“…These observations serve as a potential explanation for why low α (< 0.1) water values are not observed for particles in the ambient atmosphere (Raatikainen et al, 2013), since ambient particles are multicomponent mixtures. They also support the suggestion by Davies et al (2013) that kinetic inhibition to water uptake should rarely be observed in ambient particles, although it is possible that kinetic limitations could become more pronounced at lower temperatures, as decreasing temperature leads to increasing packing density (lower molecular area) .…”
Section: Binary Surfactant Systemssupporting
confidence: 85%
“…Previous modeling (Takahama and Russell, 2011) and experimental (Ruehl and Wilson, 2014;Davies et al, 2013) studies, along with our measurements above, indicate that there can be a kinetic limitation to water evaporation and uptake imposed by films composed of single-component surface-active organic species, in particular long-chain organic species that form solid films, which pack densely and exhibit long-range order. However, CCN measurements of ambient particles (Raatikainen et al, 2013) suggest that water uptake and droplet growth are not kinetically limited (i.e., α > 0.1) for particles sampled at a variety of locations around the world.…”
Section: Binary Surfactant Systemssupporting
confidence: 56%
“…[7] During phytoplankton bloom periods, the organic fraction dominates, contributing 63 % to the submicrometer aerosol mass, of which ,45 % is water-insoluble. [8,9] Film drops (,1 mm in diameter) produced by bursting of the bubble film efficiently transfer surface-active species that reside at the air-water interface into the atmosphere; this explains the presence of surfactants in fine SSA particles (,2.5 mm in diameter). [10] Given that the relative concentration of organic matter to inorganic salts in the ocean is extremely low (60-90 mM organic matter compared with approximately 460 000 mM Na þ ), [3] the high relative fraction of organic matter in SSA shows that the transfer of organic species from the ocean to SSA proceeds through selective processes.…”
Section: Introductionmentioning
confidence: 99%